Sisi Ekonomi Inovasi Daerah: Model Terintegrasi Komersialisasi dan Monetisasi untuk Kemandirian Fiskal Daerah - Saksono, Herie (Research and Development Agency Ministry of Home Affairs, 2025)
This study explores the economic dimension of regional innovation through developing an integrated model of commercialization and monetization to strengthen regional fiscal autonomy (RFA). Regional innovations have been predominantly viewed from a public service perspective without considering their economic potential to reduce fiscal dependence on central government. Using a qualitative approach with a case study in Kotamobagu City, which has organized the Innovative Government Award (IGA) for five consecutive years (2020-2024), this research identifies four main model components: commercialization, valuation, calculation, and monetization of regional innovations. Findings reveal that among 165 innovations produced, the majority originated from regional agencies (74 innovations or 44.85%) and the general public (50 innovations or 30.30%), yet their economic potential remains underexploited. The economic dimension of regional innovation becomes crucial in the context of fiscal decentralization as it offers sustainable alternative revenue sources based on local strengths. The integrated model developed provides a holistic framework that addresses the fragmentation of commercialization approaches while creating systematic mechanisms to transform innovations from public service instruments into strategic revenue-generating assets. The advantage of integration lies in its ability to optimize the economic value of innovations while maintaining their social and public service functions. The theoretical contribution integrates Fiscal Autonomy Theory, Economic Innovation Theory, and Innovation Commercialization Theory within the Indonesian regional government context. Practically, this model can enhance Regional Original Revenue (PAD) through diversification of innovation-based local revenue sources. Model implementation requires strengthening human resource capacity, developing supportive regulations, and establishing a dodeca-helix-based regional innovation ecosystem.